Auditory spatial attention in a complex acoustic environment while walking: Investigation of dual-task performance - Lau, Sin Tung; Maracle, Jacob; Coletta, Dario; Singh, Gurjit; Campos, Jennifer; Kathleen Pichora-Fuller, M. (Canadian Acoustics, 2012)
Auditory spatial attention in a complex acoustic environment while walking was investigated to find the dual-task performance. Three undergraduate students, ages 19 to 26 years, with normal pure-tone air-conducted hearing thresholds for frequencies from 0.25 to 8 kHz, performed a word identification task in two experimental conditions. Testing was conducted in StreetLab in the Challenging Environment Assessment Laboratory (CEAL) at the Toronto Rehabilitation Institute. The stimuli for the listening task were all sentences recorded by four male talkers for the Coordinated Response Measure (CRM). All participants completed 8 sessions in each of two conditions; standing and walking. The standing and walking conditions differed in terms of whether or not there was a secondary task during listening. The high degree of similarity in listening task performance between the standing and walking conditions suggest that the listening abilities in multi-talker environments of these participants were not affected by the inclusion of a walking component.